2005
DOI: 10.1539/joh.47.350
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Biological Monitoring in a Lead Acid Battery Manufacturing Unit in India

Abstract: Environmental and Biological Monitoring in a Lead

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
4
8
0
Order By: Relevance
“…Considering the present age of the workers and their years of job, it is evident that most of the workers were exposed to lead continuously for a long time. Studies carried out in India 16 and in Bangladesh 17 have also depicted similar picture of the working conditions and the level of education favoring our findings.…”
Section: Discussionsupporting
confidence: 88%
“…Considering the present age of the workers and their years of job, it is evident that most of the workers were exposed to lead continuously for a long time. Studies carried out in India 16 and in Bangladesh 17 have also depicted similar picture of the working conditions and the level of education favoring our findings.…”
Section: Discussionsupporting
confidence: 88%
“…Multivariate regression analysis demonstrated that exposure category had a strong explanatory capacity and was identified as strong predictor ( R 2 = 24.4%) for blood lead concentration. The similar type of findings was obtained from an Indian study on lead, where it was mentioned that mean blood lead level was significantly more in the high exposed section compared to low exposed section of the lead factory [27]. …”
Section: Discussionsupporting
confidence: 77%
“…The workers of these sections were at high risk of lead exposure because of the possibility of coming in direct contact with lead during handling of recovered lead, making and trimming new lead plates, pasting lead oxides, and finishing of new lead battery. Inhalation of lead might also occur by air borne lead particulate matter and by fumes during melting to recover lead [2427]. Further, lead exposure may occur through ingestion of contaminated food and drink and, in this study, as the workers took their food and drink in the premises.…”
Section: Discussionmentioning
confidence: 96%
“…They can therefore be considered suitable for preclinical prevention measures (second level prevention). Occupational lead exposure occurs chiefly through breathing in lead particles; there are significant correlations between worksite airborne lead exposure and blood and urinary lead in workers [ 26 , 27 ]. Limiting occupational exposure to airborne lead is more important than second level prevention.…”
Section: Discussionmentioning
confidence: 99%